(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article deals with the defining of criteria, factors and levels of the development of foreign students’ intercultural competence of intercultural communication during the Ukrainian language training. Viewpoints of scientists on the intercultural competence structure and peculiarities of the criteria choice are analyzed. Motivational-value, cognitive, professional and communicative, linguoculturological criteria of intercultural competence development were signed out. Motivational-value criterion represents the system of motives and values that promote students to master intercultural communication competences treat them as necessary in their future public and professional activities. Cognitive characterizes the achievements of foreign students, their understanding of essence, content, goals of intercultural communication. Professional and communicative criterion determines the ability to apply the acquired knowledge of the language, culture, norms of communication in practice. Linguoculturological criterion represents the level of foreign students’ language, culture, history, social and political values of the studied country awareness. The conducted research allowed to determine the levels of intercultural communication competences: reproductive, consciously-situational, active and creative.